The New Divorce Legislation in the Republic Of Croatia under the Influence of Psychology, Sociology, and International Law. (15th January 2018) - Rešetar, Branka
Abstract: Recent scientific interdisciplinary findings in the area of divorce and international law relating to children's rights have had considerable influence on the current reform of divorce in Croatia. The first aim of the Croatian legislator was to help parents reach an agreement in all matters related to their children, believing this approach could help reduce parental conflict and improve the exercise of joint parental responsibility, contact with the child, and child maintenance compliance. The second aim of the Croatian legislator was to strengthening children's procedural rights in divorce proceedings. This article is aimed at presenting the interdisciplinary trends that have influenced the Croatian legislator when introducing changes to the divorce scheme and new legal instruments: mandatory counselling, mandatory family mediation, parenting plan, neutral legal terminology, and highlighting the importance of cooperation and communication between parents. These novelties represent a new approach to divorce, putting the focus on the autonomy and responsibility of parents in the organization of family life after divorce. If the agreement on parental responsibility fails, parents will have to face court proceeding which have become more complex due to the response of the Croatian legislator to recent international requirements and guidelines aimed at effective legal protection of children's procedural rights. The child is explicitly recognized as a party in divorce proceeding, the exercise of the right of the child to be heard is clearly regulated and the child is accompanied with a special guardian who is obliged to represent child's interests in divorce proceedings.